Exchange-traded funds and transparency in over-the-counter markets - Doan, Viet-Dung (Review of Finance, 2025)
Abstract This article explores a new channel through which exchange-traded funds (ETFs) can affect underlying asset prices. In over-the-counter markets, daily disclosure of ETF portfolio holdings increases price transparency and therefore retail investors’ bargaining power. I show that ETF-held municipal bonds have significantly lower dealer markups than observationally similar non-ETF-held bonds. This effect cannot be explained by bond selection or ETFs’ own trading activity. Rather, ETFs’ disclosure of end-of-day bond pricing is associated with lower retail markups by 5–9 basis points.